Crowdfunding and Social Capital: A Pathway for The Internationalization of MSMEs and Social Enterprises? - Vergara, Kimberly Christie; Vergara, Raymond Allan (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Micro and social entrepreneurs face multiple challenges, including limited access to funding, knowledge systems, networks, and markets, which limit the growth and development of their ventures. This study seeks to understand how the participation in crowdfunding and its utilization to internationalize can help micro and social enterprises address challenges through social capital. Through a narrative review of literature anchored on the resource-based and knowledge-based theories of the firm and the theory of social capital, this study finds that crowdfunding provides access to funding, knowledge systems, and networks. Moreover, the participation in crowdfunding provides access to large, international markets. However, despite these benefits, there remains challenges to micro and social enterprise participation in crowdfunding as there is low awareness and adoption in developing countries. Furthermore, there is still question on crowdfunding’s viability as an internationalization strategy. The study ends by identifying directions for future research.